Perception of women towards contraceptive methods: using health belief model - Mohamed Mahmoud, Noha; Saber Ghaly, Asmaa; Hassan Ahmad, Afaf (International Journal of Advanced Nursing Studies, 2020)
Introduction: The Health Belief Model (HBM) is one of the major conceptual frameworks guiding current research as well as practice in the health sciences. It takes into account the multiple factors present in a personâ€™s decisions to live a healthy life, seek help when needed, and maintain periodic check-ups and screening. Aim of the study is to identify perception of women towards contraceptive methods using the health belief model. Research design: A descriptive research design was utilized in this study. Setting: This study was conducted at four family planning clinics affiliated to four maternity hospitals namely: EL- Shatby Maternity University hospital affiliated to Alexandria University, Dar-Ismail Maternity hospital affiliated to Ministry of Health, Faisal hospital affiliated to Health Insurance and Dar ALWelada hospital affiliated to Medical Health Association. Subjects: A convenience sample of 320 women who were seeking family planning services. Tools; Tool I: Contraceptive users' basic data structured interview schedule; Tool II: Contraceptive users' Health Belief scale. Results: Approximately an equal percent (56.56% & 43.44%) of the contraceptive users perceived themselves either highly susceptible or moderately susceptible for threat of getting pregnant, respectively. More than three-fourths (76.25%) of them had moderate perceived severity to the problems associated with contraceptive use compared to only 23.75% of them who had high level of perception. As much as 84.37% of them highly perceived the benefits of contraception uptake. Meanwhile, almost all (93.44%) of them moderately perceived barriers associated with contraception utilization. Conclusion: Contraceptive users had high perception related to susceptibility of the threat of pregnancy and benefits of contraceptive methods utilization. Moreover, the vast majority of them had moderate perception to severity and barriers associated with contraception uptake. Last but not least, there was a statistically significant correlation between women's health beliefs and their utilization of contraceptive method.Â